The influence of cognitive flexibility on research abilities among medical students: cross-section study - Sarah S. Almutawa; Norah A. Alshehri; Abdulrahman A. AlNoshan; Nasser M. AbuDujain; Khaled S. Almutawa; Ahmed S. Almutawa (BMC Medical Education)
Abstract Background/aim: cognitive flexibility refers to people’s capacity to change or evolve their thinking and strategies when confronted with new information or circumstances These attributes are essential in research environments where complex and dynamic challenges frequently arise. In this study, the aim is to explore and establish whether a correlation exists between cognitive flexibility and research performance, especially in the medical students, in order to fill the deficit, if any, as well as understand the status of research teaching. Methods We conducted an analytical cross-sectional study with medical students from the College of Medicine at King Saud University in Riyadh, Saudi Arabia. We requested the subjects to participate in an online questionnaire consisting of four question sections. They included demographic information, a Cognitive Flexibility Scale, knowledge, attitude, practice, and barriers to performing medical research. Results The survey received responses from 303 medical students. We judged cognitive flexibility highest in the willingness to shift to possible alternatives and lowest in the use of acquired knowledge in practical contexts. The students were aware of and had a positive attitude towards research, although only 19.5% of them had actually published. Some of the barriers included inadequate time and challenges with follow-up care for patients. It was established that there was a weak negative relationship between the scores of perceived barriers and the Cognitive Flexibility score (r = -0.217, P < 0.001). Conclusion The study has concluded that students with higher cognitive flexibility cope with the barriers better and, therefore, are likely to be in a better state of well-being. This suggests that the medical education system should include techniques like problem-based learning. Meanwhile, research efforts should aim to test more specific and accountable methods for enhancing cognitive flexibility, as well as their impact on learning and clinical practice. Clinical trial number Not applicable.